Review of the IMF's Trade Restrictiveness Index. (Policy Papers; Policy Paper, 2005)
This paper examines the construction of the index and its use over the past seven years, identifies its limitations, examines several alternative measures of trade policy, and highlights some options for improving the Fund's use of trade policy indicators.